2019
DOI: 10.4317/jced.56316
|View full text |Cite
|
Sign up to set email alerts
|

Does comsumption of staining drinks compromise the result of tooth whitening?

Abstract: Background: After dental bleaching procedures dentists commonly advise patients to reduce the consumption of beverages that may cause the teeth to stain, however, the effectiveness of teeth whitening may not be directly affected by diet. Material and Methods: It was evaluated through in vitro study whether contact with dyes through in-office bleaching sessions with 35% hydrogen peroxide would influence the effectiveness of treatment. Sixty bovine incisors were randomly assigned into 5 groups (n = 12) according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
8
0
6
Order By: Relevance
“…e mean pH in both groups showed an increase from baseline when compared to the final value, but no statistically significant difference was noted between the two groups. is stability of pH values is very important because it may have an influence on the properties of tooth enamel subjected to whitening [1]. In fact, low pH whitening toothpaste is responsible for in vitro morphological changes in the enamel [3].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e mean pH in both groups showed an increase from baseline when compared to the final value, but no statistically significant difference was noted between the two groups. is stability of pH values is very important because it may have an influence on the properties of tooth enamel subjected to whitening [1]. In fact, low pH whitening toothpaste is responsible for in vitro morphological changes in the enamel [3].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Tooth bleaching is one of the most requested esthetic treatments in dentistry [1]. It helps to reduce discoloration using chemical agents to oxidize organic molecules accumulated on the tooth surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated the influence of pigmented substances on the color of bleached teeth. To Nogueira et al 22 , the consumption of pigment drinks during the bleaching treatment can influence the speed of treatment. This surface is likely to be more susceptible to staining 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Over-the-counter products can expose patients to allergic reactions to their components, extravasation or ingestion of the whitening substance, and the occurrence of sensitivity [14,15]. In addition, bleaching agents increase the surface porosity of the enamel, induce subclinical pulp reactions and dentin hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%